Growth and pigment constituents of the red alga Gracilaria edulis (Gmelin) Silva, grown at different depths - Jayasankar, Reeta; Varghese, Sally (Indian Journal of Fisheries, 2011)
Chlorophyll-a, phycoerythrin, phycocyanin and allophycocyanin of the red alga,Gracilaria edulis, cultured in outdoor tanks under natural light at different depthswere estimated. Crop growth rate and pigment contents in relation to varjdnglight intensities (depth) were observed. An inverse relationship between pigmentcontent and the light intensity was noted. But growth rate was more at higherlight intensities.